Stoichiometric dependence and laser heating effect on the luminescence thermometric performance of Er3+, Yb3+: YuGdwVO4 microparticles in the non-saturation regime. (July 2022) - Bhiri, Nisrin Mohamed; Dammak, Mohamed; Carvajal, Joan Josep; Aguiló, Magdalena; Díaz, Francesc; Pujol, Maria Cinta
Highlights: Different calculation methods (OriginLab@software and TeSen Calculator tool) based on the fluorescence intensity ratio were investigated to determine the thermometric performance of Er 3+, Yb 3+ : Yu Gdw VO4 MCs. Best thermometric performance can be achieved under lower excitation power density and for host material with higher atomic concentration of Gd 3+ ions. Whenever the atomic concentration of Gd 3+ ions is higher than the one of Y 3+ ions, whenever the lattice expanded, whenever the lattice field surrounding the sensitive Er 3+ ions is less important and then the thermometric performances are more efficient. Whenever the ∆E FIR and the ∆E TS values are lower than the ∆E` experimental, whenever the sample is heated and then the thermometric parameters are less competitive. Abstract: The performance of Yu Gdw VO4 microcrystals with different atomic concentrations of Y 3+ and Gd 3+ ions, co-doped Er 3+ -Yb 3+, as thermometers, exploiting two different calculation methods based on the fluorescence intensity ratio is investigated in the non-saturation regime. At a low excitation power density of 20 W cm −2, the thermometric parameters are approximately the same for all the analyzed sensors. Whereas for an excitation power density of 155 W cm −2, they are widely different all along the 303–513 K temperature range of study. Such as an increase on the Gd 3+ ion concentration in the microcrystals induces a lattice expansion that can result in the decreasing of the lattice field surrounding the Er 3+ ions and then it could enhance greatly the thermometric performances. For both calculation methods, it has been demonstrated that the ∆E FIR (fitted from the FIR curves) and the ∆E TS (determined using the TeSen Calculator program) values are lower than the ∆E` experimental (fitted from the emission spectra measured at room temperature), whenever the sample is heated and then the thermometric parameters are less competitive. Graphical abstract: Image, graphical abstract Stoichiometric and laser heating effects on the Crystal structural and thermometric features of the Er 3+, Yb 3+ : Yu Gdw VO4 microparticles.